Dose–response associations between metabolic indexes and the risk of comorbid type 2 diabetes mellitus among rheumatoid arthritis patients from Northern China: a case–control study - Ying Li; Guangxiao Li; Weijun Chi; Bingqing Bai; Tingting Wei; Lingyu Fu (BMJ Open)
Objective To investigate whether there were any differences in the patterns of metabolic abnormalities between patients with rheumatoid arthritis (RA) with comorbid type 2 diabetes mellitus (T2DM) and other populations, and to plot the dose–response relationships between metabolic indexes and the risk of comorbid T2DM among patients with RA.Design and setting This is a retrospective case–control study using electronic medical records (EMRs). Patients with RA and/or T2DM or controls who were admitted to the First Affiliated Hospital of China Medical University between April 2008 and December 2016 were retrospectively recruited through the EMR system. After age-matching and sex-matching, 261 controls, 274 patients with T2DM, 276 patients with RA and 151 patients with RA+T2DM were eventually recruited.Results Patients with RA+T2DM exhibited higher levels of systolic blood pressure (SBP), fasting plasma glucose (FPG) and triglyceride (TG) than the RA only patients. Moreover, the proportions of impaired fasting glucose (IFG), and total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-C) dyslipidaemia in the RA+T2DM group were higher than those in the RA alone group (for IFG: 28.48% vs 18.84%, p=0.02; for TC: 25.17% vs 15.22%, p=0.01; for LDL-C: 25.83% vs 17.03%; p=0.03). Rheumatoid factor (RF) positivity and IFG were independent risk indicators for comorbid T2DM among patients with RA (for RF positivity: OR=0.45; 95% CI: 0.29 to 0.69; p<0.001; for IFG: OR=1.70; 95% CI: 1.04 to 2.76; p=0.03).Conclusion Linear dose–response associations between SBP, TC, TG and the risk of comorbid T2DM among patients with RA were observed, whereas a non-linear dose–response association between FPG and the risk of comorbid T2DM was found. Patients with RA+T2DM were more likely to exhibit metabolic abnormalities than RA only patients. Patients with RA+T2DM with metabolic abnormalities deserve more attention from rheumatologists and endocrinologists.